The Yankee at the seder - Weber, Elka, 1968- (Tricycle Press, 2009)
As a Confederate family prepares for Passover the day after the Civil War has ended, a Yankee arrives on their Virginia doorstep and is invited to share their meal, to the dismay of ten-year-old Jacob. Includes historical notes about Corporal Myer Levy, on whom the story is based, and his prominent Philadelphia family.